Comprehensive Value Chain Analysis of Women-Led Community Based Rice Seed Entrepreneurship Model in Bangladesh - Nuruzzaman; Afrad, Md. Safiul Islam; Habib, Muhammad Ashraful; Nayak, Swati; Haque, Md. Enamul; Hoque, Muhammad Ziaul; Nahar, Mst. Ashrafun; Mohapatra, Subhasmita; Biswas, Amlan (International Rice Research Institute, 2026)
Rice seed production offers an avenue to involve local entrepreneurs, particularly women, across the entire value chain through the Women-led Community-Based Rice Seed Entrepreneurship Model (WLCBRSEM). This study analyzes the primary actors within the WLCBRSEM value chain, comparing their value addition with that of conventional rice seed systems, while identifying key challenges. Market margins and value addition were calculated for each stakeholder using standard formulas. Results indicate that after harvest and initial processing, Seed Producer Groups (SPGs) sell seeds to the Seed Management Group (SMG) of the Executive Committee (EC) at BDT 35.0 per kg. The SMG then threshes, dries, sorts, and packages the seeds, producing Certified Seeds (CS) approved by the Seed Certification Agency (SCA), achieving up to 71.43% value addition before sale. These seeds are subsequently distributed to registered dealers, who add 5.33–9.33% value and sell them at BDT 82–85 per kg. SPGs retain a portion of seeds for the following season to maintain continuity. While the model enhances seed quality and empowers women, challenges such as lack of moisture meters and limited weather information constrain the WSPGs’ efficiency.